Power and thrust capping of tidal stream turbines: a case study of the Pentland Firth - Wang, T; Adcock, TAA (American Society of Mechanical Engineers, 2018)
It will not be practical for tidal stream turbines to extract all the peaks in energy over the tidal cycle. It is widely assumed that some form of power capping strategy will be required. In this paper we examine this using a 2D shallow water model of tidal hydrodynamics of the Pentland Firth. We argue that in addition to power capping, it is sensible to control the turbines to limit the peak thrust on them. We show that this can lead to a significant reduction in the peak thrust applied to the turbines and smaller changes to the naturally occurring flow rate whilst having a minimal effect of the mean power generated.